Sexual behavior among Brazilian adolescents, National Adolescent School-based Health Survey (PeNSE 2012) - Maryane Oliveira-Campos; Marília Lavocart Nunes; Fátima de Carvalho Madeira; Maria Goreth Santos; Silvia Reise Bregmann; Deborah Carvalho Malta; Luana Giatti; Sandhi Maria Barreto (Associação Brasileira de Pós-Graduação em Saúde Coletiva, 2014)
OBJECTIVE: This study describes the sexual behavior among students who participated in the National Adolescent School-based Health Survey (PeNSE) 2012 and investigates whether social inequalities, the use of psychoactive substances and the dissemination of information on sexual and reproductive health in school are associated with differences in behavior. METHODOLOGY: The response variable was the sexual behavior described in three categories (never had sexual intercourse, had protected sexual intercourse, had unprotected sexual intercourse). The explanatory variables were grouped into socio- demographic characteristics, substance use and information on sexual and reproductive health in school. Variables associated with the conduct and unprotected sex were identified through multinomial logistic regression, using "never had sexual intercourse" as a reference. RESULTS: Over nearly a quarter of the adolescents have had sexual intercourse in life, being more frequent among boys. About 25% did not use a condom in the last intercourse. Low maternal education and work increased the chance of risky sexual behavior. Any chance of protected and unprotected sex increased with the number of psychoactive substances used. Among those who don't receive guidance on the prevention of pregnancy in school, the chance to have sexual intercourse increased, with the largest magnitude for unprotected sex (OR = 1.41 and OR = 1.87 ). CONCLUSION: The information on preventing pregnancy and STD/AIDS need to be disseminated before the 9th grade. Social inequalities negatively affect risky sexual behavior. Substance use is strongly associated with unprotected sex. Information on the prevention of pregnancy and STD/AIDS need to be disseminated early.